E-MathBook Lampung: Inovasi E-Book Etnomatematika Berbasis Budaya Lokal - Pratiwi, Dona Dinda; Anggoro, Bambang Sri Anggoro; Aini, Fitri Nur (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Students are more interested in learning mathematics by utilizing technology that is connected to Lampung culture to increase students' knowledge and insight in learning. This study aims to develop a mathematics e-book based on Lampung cultural ethnomathematics in the ability to understand concepts in flat shape material. This study uses a research and development type of research with the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The development stage involves validators (media expert validators, material expert validators, and question expert validators) to assess the feasibility of good and correct e-books. The implementation stage involves students to test the effectiveness of the e-book using pretest and posttest questions for conceptual understanding. The results of the validation of the e-module by media expert validators, validation by material expert validators, validation by question experts were declared valid by the experts. Meanwhile, the small group attractiveness trial and the large group attractiveness trial were declared very interesting by the students. For the effectiveness test using the N-Gain test and getting a moderate criterion value, it can thus be concluded that the development of a mathematics e-book based on Lampung cultural ethnomathematics in the ability to understand concepts in flat shapes is effective in improving students' conceptual understanding so that students are interested and active during the mathematics learning process which makes students not bored.